Suicide menace in North-Eastern India: a hospital-based study on the clinical aspects of suicide attempters - Robin Victor; Chiradeep Sengupta; Subrata Naskar; Bhanita Boro; Kaveri Saxena (Open Journal of Psychiatry and Allied Sciences, 2017)
Context: Suicide is a rapidly evolving public health problem affecting people worldwide and is the second leading cause of death among 15-29 year olds globally in 2012. It is a multidimensional and multifactorial phenomenon in terms of the cause and the effect. Objectives: To find out sociodemographic profiles, modes of attempting suicide, and prevalence of depression among the subjects with suicide attempt, and to find any association between them. Methods: One hundred and eight cases of attempted suicide were selected consecutively who were attending the hospital irrespective of the department and were evaluated to find out various sociodemographic variables, methods of attempting suicide, and if they fulfilled ICD-10 criteria for depressive disorder. Results: Higher prevalence of suicide was seen in cases with age <35 years (77.6%), female gender (54.62%), from rural background (69.44%), living in nuclear family (64.81%), who were unmarried/single (60.18%), illiterate or having education up to class Xth (71.29%), occupationally dependent (68.51%), belonging to lower/lower middle socioeconomic class (51.85%). Organophosphorus poisoning (42.59%) was the most common method of attempting suicide. 66.66% of cases suffered from depressive disorder at the time of attempting suicide. Poisoning was the more common method among cases with age less than 35 years (63.09%) and while males opted for drug overdose (16.32%) females used poisoning (64.40%) as the most common method to attempt suicide. Conclusions: The data provides a range of information to identify vulnerable groups so that a multidimensional approach can be planned for formulation of suicide prevention strategies.